Image analysis software versus direct anthropometry for breast measurements - Quieregatto,Paulo Rogério (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE: To compare breast measurements performed using the software packages ImageTool(r), AutoCAD(r) and Adobe Photoshop(r) with direct anthropometric measurements. METHODS: Points were marked on the breasts and arms of 40 volunteer women aged between 18 and 60 years. When connecting the points, seven linear segments and one angular measurement on each half of the body, and one medial segment common to both body halves were defined. The volunteers were photographed in a standardized manner. Photogrammetric measurements were performed by three independent observers using the three software packages and compared to direct anthropometric measurements made with calipers and a protractor. RESULTS: Measurements obtained with AutoCAD(r) were the most reproducible and those made with ImageTool(r) were the most similar to direct anthropometry, while measurements with Adobe Photoshop(r) showed the largest differences. Except for angular measurements, significant differences were found between measurements of line segments made using the three software packages and those obtained by direct anthropometry. CONCLUSION: AutoCAD(r) provided the highest precision and intermediate accuracy; ImageTool(r) had the highest accuracy and lowest precision; and Adobe Photoshop(r) showed intermediate precision and the worst accuracy among the three software packages.